Ambientes Imersivos na Medicina Dentária - Eduardo de Matos Pedro (2020)
Virtual reality has been engaged a lot in the entertainment area, each day more and more games are created to be used with virtual reality devices. This is undoubtedly an area in constant development and which shows improvements every year. Virtual reality, in addition to being effective in the entertainment world, is also effective in the field of psychotherapy, more specifically in the treatment of phobias. This project aims to identify how virtual reality can help children overcome their anxiety about going to the dentist, through the use of an immersive interactive environment to be used together with virtual reality glasses during a dental intervention. In addition to treating / relieving this anxiety and helping children to have fun, it will also educate them to have better oral hygiene. The methodology for this investigation consists of the use of interviews with children during and after the use of the prototype at Faculdade de Medicina Dentária da Universidade do Porto, to understand the behaviors and to get the opinions. Once this information is structured, it is necessary to analyze and understand whether it helped and how it helped children to abstract themselves from the dental procedure and what can be improved in future versions. This study is especially relevant to the areas of psychotherapy with virtual reality, that is, the use of virtual environments to abstract people in their painful treatments and to treat phobias.